2008
DOI: 10.1002/anie.200704078
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Vesicles Containing Small Vesicles within Interior Aqueous Compartments and pH‐Responsive Transmembrane Channels

Abstract: Multivesicle assemblies with pH‐responsive transmembrane channels in the vesicle walls (see picture) were made by two‐step double emulsion of copolymers comprising acrylic acid and acrylate of 1,2‐distearoyl‐rac‐glycerol. These assemblies mimic eukaryotic cells, which contain functional organelles within the cell walls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(120 citation statements)
references
References 36 publications
1
117
0
2
Order By: Relevance
“…Moreover, targeted transport can be achieved by taking advantage of the many possibilities to endfunctionalize the copolymers (5). The controlled release of therapeutic substances can also be integrated through the use of copolymers with blocks that respond to chemical stimuli such as hydrolysis (6,7), oxidation (8) or reduction (9) reaction, and pH changes (10)(11)(12)(13)(14)(15)(16)(17). Common strategies have been to use hydrophobic blocks that can progressively degrade or convert into hydrophilic moieties or to use a cleaveable linkage between hydrophobic and hydrophilic blocks.…”
mentioning
confidence: 99%
“…Moreover, targeted transport can be achieved by taking advantage of the many possibilities to endfunctionalize the copolymers (5). The controlled release of therapeutic substances can also be integrated through the use of copolymers with blocks that respond to chemical stimuli such as hydrolysis (6,7), oxidation (8) or reduction (9) reaction, and pH changes (10)(11)(12)(13)(14)(15)(16)(17). Common strategies have been to use hydrophobic blocks that can progressively degrade or convert into hydrophilic moieties or to use a cleaveable linkage between hydrophobic and hydrophilic blocks.…”
mentioning
confidence: 99%
“…For vesicles formed from a PAA-b-PBD diblock copolymer in water, Discher's group (Geng et al 2005) observed that a sudden increase in pH induced the rapid (~min-utes) transition of vesicles into worms and spheres. Chiu's group has recently reported an interesting work on polymersomes with pH-responsive transmembrane channels (Chiu et al 2008). The copolymers used to form vesicles were not block copolymers but rather random copolymers of acrylic acid (AAc) and distearin acrylate (DSA), that were obtained from partial transesterification of poly(N-acryloxysuccinimide) (poly(NAS)) with distearin (a lipid graft) followed by thorough hydrolysis of the un-reacted NAS to AAc units.…”
Section: Ph Responsive Polymersomes Formed From Synthetic Block Copolmentioning
confidence: 99%
“…[24] In a study by Chiu et al, pH-responsive acrylic acid (AAc) channels were arranged in the vesicle membrane and the open or the closed state of the channels could be controlled by adjusting the pH value of the aqueous solution. [26] Similarly, bacterial pore proteins were set throughout the vesicles and an intelligent nanometer-scale sensoreffector was built by Hunziker and co-workers. [27] The bacterial channel forming protein, LamB could also be constituted in ABA-triblock copolymer vesicles.…”
Section: Introductionmentioning
confidence: 99%